Knowledge, attitude towards human papillomavirus and HPV vaccine among medical students of a tertiary care teaching hospital in India - Tripathy, Saswati; Mohapatra, Satyajit; Muthulakshmi, M.; Rani, R. Jamuna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to assess the awareness of the human papillomavirus (HPV) infections and vaccination among the young students of a tertiary care teaching hospital. Methods: A cross sectional study was done among the students of a tertiary care teaching hospital. The students were assured of the confidentiality and were provided a questionnaire about HPV infection and HPV vaccine. Results: About 94.3% of students implicated that HPV is a causative agent of cervical cancer and 5.7% students didn’t know about the association. About 72.1% were aware of the availability of the vaccine to be immunized against HPV infection but 3.3% answered wrongly and 24.6% didn’t know about it. Thirty one percent students knew the correct age of initiation of the vaccination, 23% answered wrongly and about 45.9% of the students didn’t know the answer. Only 4.1 % of the students have been vaccinated with HPV vaccine. About 63.9% students didn’t agree to vaccinate themselves against HPV as they felt it would give a false sense of security and 68.8% of the students were against the routine vaccination of the young Indian population against HPV as the sexual exposure occurs at late age. 73% students referred the age of vaccination to be >25 years. Conclusions: Lack of knowledge among medical students can be detrimental to the health of the society. So there is a need to create awareness among the future health educators against various aspects of HPV, cervical cancers and its prevention.